A new lethal syndrome of exomphalos, short limbs, and macrogonadism. Issue 2 (1st February 1999) - Faivre, Laurence; Delezoide, Anne-Lise; Narcy, Françoise; Razavi, Féréchté; Bouvier, Raymonde; Cormier-Daire, Valérie; Briard, Marie-Louise; Lyonnet, Stanislas; Vekemans, Michel; Munnich, Arnold; Le Merrer, Martine
Abstract : We report a new lethal multiple congenital abnormality (MCA) syndrome of exomphalos, short limbs, nuchal web, macrogonadism, and facial dysmorphism in seven fetuses (six males and one female) belonging to three unrelated families. X rays showed enlarged and irregular metaphyses with a heterogeneous pattern of mineralisation of the long bones. Pathological examination showed adrenal cytomegaly, hyperplasia of Leydig cells, ovarian stroma cells, and Langherans cells, and renal microcysts. We suggest that this condition is a new autosomal recessive MCA syndrome different from Beckwith-Wiedemann syndrome, especially as no infracytogenetic deletion or uniparental disomy of chromosome 11 was found.